The role of Japanese governmental organizations in cooperation in education: the case of Kazakhstan: THE CASE OF KAZAKHSTAN - Rustemova А. (Journal of Oriental Studies, 2021)
Cooperation in education with high income countries is becoming more essential than ever. However, Kazakhstan is still falling short in development of educational cooperation with some of the high-income countries in the world as Japan. This paper aims to clarify the role of Japanese governmental organizations in development of bilateral in Kazakh-Japan relationship as well as educational cooperation between the two states. A historical and systematic analysis was used , for a better understanding the policy of Japanese educational organizations in Kazakhstan. Along with official information of embassies, the annual reports of a Kazakhstani university were used to conduct the research. In general, the Japanese governmental organizations play a crucial role as actors that foster cultural integration, political relations and peace-building. However, promotion of Japanese traditions and Japanese language education can have an aim of strengthening its influence and prestige in Kazakhstan. Yet, especially in the case of Japan and Kazakhstan, it is far from being a hegemony tool of a dominant country. The results of this study may be useful for everyone who is interested in cooperation in education, Kazakhstan-Japan relations, internationalization of higher education in Kazakhstan and the role of governmental bodies in these processes. Keywords: cooperation in education, internationalization, Japan, Kazakhstan, governmental organizations.